La cuestión del monarca hegeliano: necesidad de un análisis inmanente - Hurtado Blandón, Andrés Felipe (2019)
“The Question of the Hegelian Monarch: Necessity for an Immanent Analisys.”. Among many aspects for which Hegel’s philosophy is known, his characterization and defense of a constitutional and hereditary monarchy in his Elements of the Philosophy of Right has been, undoubtedly, one of the most discussed issues. Considering the wide conflict between positions, approaches and interpretations, as well as the difficulty that many of Hegel’s assertions embody in this respect, it can be said that the problem about the true meaning of monarchy in his philosophy, is still unsolved in many aspects. The purpose of this text is not to reconstruct the main interpretations, but rather identify what are the perspectives or models of analysis, which have been at its base. This, in order to contrast them with Hegel’s methodological caveats in his work and justify, from there, the need to prioritize and give a better development to a perspective and specific way of addressing the issue. In the end, some methodological considerations and suggestions for such analysis will be offered, which could help to find new answers or elements of interpretation in this respect.